Officially Supported Export Credits; Developments and Prospects, May 1990. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1988)
This paper emphasizes on the policy reaction of the agencies and their authorities to countries in various stages of debt-servicing difficulties. Export credit agencies have, over the past few years, been adopting a progressively more open stance. This is true with respect to short-term cover generally and, with respect to medium-term cover, for countries that have rescheduled their debts but are implementing adjustment programs and adhering to Paris Club agreements. Despite the more open stance, the volume of new medium-term credit and cover commitments to developing countries appears to have fallen off sharply over the past two years. Although for some debtors the operative constraint is clearly on the supply of new credits and cover, this is not the general case and, indeed, agencies reported net repayments from some countries for which they were wide open for new business. A number of agencies also considered that a factor behind the decline in both investment and export credits to support that investment could be the terms on which such credits are available.